PULMONARY TUBERCULOSIS AND IRON DEFICIENCY ANEMIA, IN A TERTIARY CARE HOSPITAL, ODISHA: A CROSS-SECTIONAL STUDY. - Das, Debaranjan; Sahoo, Srinibas; Dhanurdhar, Yera; Behera , Sarat ku.; Meher , Surjya Shankar (Student's Journal of Health Research Africa, 2024)
Background: Tuberculosis is a pulmonary infection that is a global health concern it affects a wide range of people worldwide. This infectious disease is contagious and spreads through droplets in the air. Methods: 52 patients participated in this study 19 among them female and 33 were males. The study was conducted O.P.D. and I.P.D. in the P.G. department of Pulmonary, Hitech Medical College and Hospital, Bhubaneswar. In the period of 7 months from January 2023 to July 2023. This was a cross-sectional study in a hospital setting. The participants were analyzed for tuberculosis and hematological parameters. The data obtained was statistically analyzed and the correlation was determined. Results: Female patients' ages ranged from 21 to 64, averaging 31 years, while males were 28 to 85 years old, averaging 52. Approximately 45% had +1 sputum microscopy results. Significant associations with tuberculosis diagnosis were found in hemoglobin levels, leukocyte count, serum ferritin, iron levels, CRP, and total iron-binding capacity (p < 0.01). Neutrophil and lymphocyte counts peaked at 70 and 28, respectively. The study showed increased ferritin and CRP levels, indicating inflammation and infection, and a notable anemia prevalence, underscoring the need for an integrated treatment approach. Conclusion: The study reveals elevated ferritin and CRP levels, alongside a significant prevalence of anemia in tuberculosis patients, highlighting the disease's systemic impact. These findings advocate for incorporating hematological parameters in tuberculosis diagnostics, underlining the need for integrated treatment approaches to enhance patient care and outcomes. Recommendation: Anaemia is often associated with pulmonary tuberculosis. Iron supplementation can help in the management of tuberculosis with anemia.